Exploring patients' and carers' views about the clinical use of ketamine to inform policy and practical decisions: mixed-methods study. Issue 4 (July 2019) - Jilka, Sagar; Murray, Claire; Wieczorek, Ania; Griffiths, Helena; Wykes, Til; McShane, Rupert
Abstract : Background: Only one-third of patients with major depressive disorder achieve remission. One new and promising treatment, ketamine, may prove challenging to implement because of its abuse potential. Although clinicians' views have been sought, we need patients' views before large scale roll-out is considered. Aims: To explore patients' and carers' views to inform policy and practical decisions about the clinical use of ketamine. Method: We carried out a mixed-methods study using data from 44 participants in 21 focus groups in three sessions and an online survey with patients, carers and advocates during a consultation day. Focus groups explored participant's views about ketamine as a form of treatment and the best way for ketamine to be prescribed and monitored. The qualitative data were analysed by two patient–researchers using an exploratory framework analysis and was supplemented by a survey. Results: The ten themes generated were monitoring, information, effect on daily life, side-effects, recreational use, effectiveness, appropriate support, cost, stigma and therapy. Participants wanted better evidence on the safety of ketamine after long-term use and felt that monitoring was required. Collecting this information would provide evidence for ketamine's safe use and administration. There were, however, concerns about the misuse of this information. Practical issues of access were important: repeated travelling to clinics and a lack of sufficiently informed medical staff were key barriers. Conclusions: Clinicians have some similar and some different views to those of patients, carers and advocates, which need to be considered in any future roll-out of ketamine. Declaration of interest: R.M. has had UK National Institute for Health Research grant funding to study ketamine, is participating in trials of esketamine, runs a clinic that provides ketamine treatment, and has consulted for Johnson & Johnson and Eleusis.